A mild TCEP-based para-azidobenzyl cleavage strategy to transform reversible cysteine thiol labelling reagents into irreversible conjugates. Issue 25 (20th November 2014) - Maruani, Antoine; Alom, Shamim; Canavelli, Pierre; Lee, Maximillian T. W.; Morgan, Rachel E.; Chudasama, Vijay; Caddick, Stephen
Abstract : A mild TCEP-based para -azidobenzyl cleavage strategy transforms reversible cysteine thiol labelling reagents into irreversible conjugates. Abstract : It has recently emerged that the succinimide linkage of a maleimide thiol addition product is fragile, which is a major issue in fields where thiol functionalisation needs to be robust. Herein we deliver a strategy that generates selective cysteine thiol labelling reagents, which are stable to hydrolysis and thiol exchange.